TrichoGate: An Improved Vector System for a Large Scale of Functional Analysis of Trichoderma Genes - Nogueira-López, Guillermo; Padilla-Arizmendi, Fabiola; Inwood, Sarah; Lyne, Sarah; Steyaert, Johanna M.; Nieto-Jacobo, Maria Fernanda; Stewart, Alison; Mendoza-Mendoza, Artemio (Frontiers in Microbiology, 2019)
Species of the genus Trichoderma are ubiquitous in the environment and are widely used in agriculture, as biopesticides, and in the industry for the production of plant cell wall-degrading enzymes. Trichoderma represents an important genus of endophytes, and several Trichoderma species have become excellent models for the study of fungal biology and plant-microbe interactions; moreover, are exceptional biotechnological factories for the production of bioactive molecules useful in agriculture and medicine. Next-generation sequencing technology coupled with systematic construction of recombinant DNA molecules provides powerful tools that contribute to the functional analysis of Trichoderma genetics, thus allowing for a better understanding of the underlying factors determining its biology. Here, we present the creation of diverse vectors containing i) promoter-specific vectors for Trichoderma, ii) gene deletions (using hygromycin phosphotransferase as selection marker), iii) protein localization (mCherry and eGFP, which were codon-optimized for Trichoderma), iv) gene complementation (neomycin phosphotransferase) and v) overexpression of encoding gene proteins fused to fluorescent markers, by using the Golden Gate technology. Furthermore, we present the design and implementation of a binary vector for Agrobacterium-mediated transformation in Trichoderma to increase the homologous recombination rate and the generation of a novel selection marker based on carboxin resistance.